Ethics, Power, Code: Divergent Bibliometric Trajectories of OpenAI and DeepSeek in the Silicon Valley-Shenzhen AI Race - Rony Kurniawan Pratama (Airlangga University, 2026)
This study elucidates the opposing bibliometric trajectories of OpenAI and DeepSeek during the Silicon Valley-Shenzhen AI race by exploring how ethics, power, and geopolitical narratives shape the global AI discourse. Based on 126 English language publications in Scopus (2015–2024) and guided by the PRISMA systematic review methods and VOSviewer science mapping, our study identifies a surge of scholarly outputs after 2021, fuelled by ChatGPT's emergence and China's advancing AI sovereignty agenda. The findings show sharp distinctions in knowledge production: OpenAI-related studies mainly involve Western academic institutions in ethical debates on existential risks and the ethical safeguards needed, while DeepSeek-related studies champion practical implementation in collaboration with Chinese tech conglomerates and state-affiliated universities. Geopolitical framings position OpenAI as an embodiment of Silicon Valley's